2023
DOI: 10.1002/adfm.202210512
|View full text |Cite
|
Sign up to set email alerts
|

Immobilizing Poly(vinylphenothiazine) in Ketjenblack‐Based Electrodes to Access its Full Specific Capacity as Battery Electrode Material

Abstract: Organic batteries are considered as environmentally friendly alternative to lithium‐ion batteries due to the application of transition metal‐free redox‐active polymers. One well‐established polymer is poly(3‐vinyl‐N‐methylphenothiazine) (PVMPT) with a fast reversibility of the electrochemical redox reaction at a potential of 3.5 V versus Li|Li+. The oxidized PVMPT is soluble in many standard battery electrolytes, which diminishes its available specific capacity but at the same time can lead to a unique charge/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Compared to the state-of-the-art conductive carbon Super C65 employed in many organic battery electrodes, Ketjenblack EC-300J and EC-600J resulted in a 3D structure of the electrode. The studies demonstrate that a dense packing of the carbon particles in the electrode is decisive for the stable immobilization of PVMPT while maintaining its long-term cycling performance …”
Section: Polymers As Separator Electrolytementioning
confidence: 95%
See 2 more Smart Citations
“…Compared to the state-of-the-art conductive carbon Super C65 employed in many organic battery electrodes, Ketjenblack EC-300J and EC-600J resulted in a 3D structure of the electrode. The studies demonstrate that a dense packing of the carbon particles in the electrode is decisive for the stable immobilization of PVMPT while maintaining its long-term cycling performance …”
Section: Polymers As Separator Electrolytementioning
confidence: 95%
“…The studies demonstrate that a dense packing of the carbon particles in the electrode is decisive for the stable immobilization of PVMPT while maintaining its long-term cycling performance. 72 A possibility offered by its synthetic versatility is the development of polymers that show several redox groups in the same polymer backbone. This allows that the same polymer material could be used as an anode and cathode simultaneously in a symmetric organic battery configuration.…”
Section: Redox Polymers Toward New Battery Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the host for Bi SACs, we used commercially available conductive carbon black, Ketjenblack EC-300 J, which is an industrial by-product possessing a low electrical resistivity (0.01-0.1 Ω • cm), high specific surface area (988 m 2 /g), [16] and weak native activity for electrochemical conversion. To synthesize Bi SACs anchored on this carbon support, a solution-based chemical method, [17] followed by inert atmosphere annealing, was used.…”
Section: Materials Synthesismentioning
confidence: 99%
“…The crosslinked derivatives were synthesized as previous studies have shown that linear PT-based polymers tend to be soluble in battery electrolytes in their oxidized form. 66,69,70 Linear PSDMPT exhibits a theoretical specific capacity of Qtheo = 148.3 mAh g −1 for a two-electron transfer.…”
Section: Synthesismentioning
confidence: 99%